'Cyber' semantics: why we should retire the latest buzzword in security studies. Issue 2 (4th May 2018) - Futter, Andrew
ABSTRACT: The word 'cyber' has become one of the most ubiquitous and powerful concepts in contemporary security studies. Very few academic papers or workshops in the social sciences fail to touch upon the 'cyber challenge' in some way, and very few politicians fail to use the term when talking about the most pressing threats to national security. But surprisingly, little consensus exists about what the term includes, refers to, or how it is being used differently by different people in different contexts. Indeed, there is no single definition or research agenda that all adhere to. This in turn often drives hype and leads to misunderstanding and bad policy. The result is that formulating suitable policies to deal with and respond to threats to digital computers and networks, either domestically or internationally, has become disjointed and obfuscated, with straw-man arguments based on erroneous assumptions often prevailing. This paper unpacks and explains these problems, before making the case for jettisoning the word 'cyber' from the security studies lexicon and returning instead to the language first developed by computer science in the 1990s. Only by doing this can we properly begin to understand, manage and mitigate the security challenges of the latest information age.